The moderating influence of property legislation on planning policy and urban form - Davies, Amanda; Atkinson, M. (Sage Publications Ltd., 2012)
This paper investigates the role that property titling legislation has had on the form of high-density residential development. A conceptual framework is developed for theorising the role of property legislation in moderating the impact of urban land use policy. It is argued that the impact of legislation on urban form is much more significant and direct than is often implied or suggested in reviews of planning policy. It is argued that property legislation has a greater role than simply supporting the implementation of urban planning policy. Property legislation has a moderating influence on policy and provides a barrier to the implementation of urban policy. To support this argument, the paper considers the development and implications of Western Australia’s strata titling legislation for the form of high-density development in that state’s capital city.